Court/Judicial records as a historical source to analyse labor relations - Lemiez, Griselda (Revista General de Información y Documentación, 2019)
In the following article, the data on labor conflicts in court records that occurred in thecement companies of Olavarría (Buenos Aires, Argentina) will be analyzed.A selection of records was made that find a direct relationship with the reconstruction of conflicts, aspart of labor relations in the cement industry, during the period 1940-1970.We believe that the application of these unique sources to various studies will allow us to assess theimportance of their use and enrich historical research.
Keywords: judicial/court records; historical sources; conflict; labor relations; workers